(untitled) (Economics and region, 2024)
The article explores the importance and positive impact of fostering and supporting startups in educational institutions. The authors examine various cases of successful incubation and implementation of innovative projects that have emerged in university environments, providing insights into the key success factors of these projects. The article meticulously analyzes the strategies and methods that have helped these startups succeed, focusing on aspects such as selecting promising ideas, forming effective teams, ensuring financial stability, and implementing efficient marketing strategies. Additionally, the article sheds light on important factors that have contributed to the successful development of startups in educational institutions, including support from university administration, the presence of infrastructure for innovation support, and access to mentorship. The authors of the article draw conclusions and formulate recommendations for further improving the conditions for supporting and fostering the startup environment in higher education institutions. These recommendations may include expanding the support program for student enterprises, attracting additional sources of funding, and increasing the accessibility of resources for student entrepreneurs. Additionally, the article discusses an innovative approach to promoting the development of startups at the Sikorsky Challenge Start-up School of the National University "Yuri Kondratyuk Poltava Polytechnic". The authors investigate the organization of the Junior START-UP 2023 competition, designed for first-year students. Over a period of more than two months in 2023, a process of training and preparation for startups from various institutes and faculties of the university was conducted. Twenty-one teams and over 100 students from various specialties participated in the competition, motivated to compete for a prize fund of 10,000 hryvnias provided by the university leadership. Overall, the article focuses on creating a conducive environment for entrepreneurship and innovation in university institutions and provides specific recommendations to achieve this goal.